Metabolic reprogramming in breast cancer results in distinct mitochondrial bioenergetics between luminal and basal subtypes. (5th February 2019) - Lunetti, Paola; Di Giacomo, Mariangela; Vergara, Daniele; De Domenico, Stefania; Maffia, Michele; Zara, Vincenzo; Capobianco, Loredana; Ferramosca, Alessandra
Abstract : Mitochondrial dysfunction is a key feature of cancer and is frequently associated with increased aggressiveness and metastatic potential. Recent evidence has brought to light a metabolic rewiring that takes place during the epithelial‐to‐mesenchymal transition (EMT), a process that drives the invasive capability of malignant tumors, and highlights a mechanistic link between mitochondrial dysfunction and EMT that has been only partially investigated. In this study, we characterized mitochondrial function and bioenergetic status of cultured human breast cancer cell lines, including luminal‐like and basal‐like subtypes. Through a combination of biochemical and functional studies, we demonstrated that basal‐like cell lines exhibit impaired, but not completely inactive, mitochondrial function, and rely on a consequent metabolic switch to glycolysis to support their ATP demand. These altered metabolic activities are linked to modifications of key electron transport chain proteins and a significant increase in levels of reactive oxygen species compared to luminal cells. Furthermore, we observed that the stable knockdown of EMT markers caused functional changes in mitochondria that result in acquisition of a hybrid glycolysis/OXPHOS phenotype in cancer cells as a means to sustain their metabolic demand. Abstract : We report a detailed biochemical and functional characterization of energy metabolism in breast cancer cell line models. Basal‐like cell lines exhibit impaired, but not completely inactive, mitochondrial function, and rely on a consequent metabolic switch to glycolysis to support their ATP demand. Furthermore, the stable knockdown of epithelial‐to‐mesenchymal transition markers caused functional changes in mitochondria, resulting in acquisition of a hybrid glycolysis/OXPHOS phenotype in cancer cells.